2002
DOI: 10.1152/ajpheart.00130.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACh and adenosine mediated by Kir3.1 and Kir3.4 on ferret ventricular cells

Abstract: The inotropic effects of ACh and adenosine on ferret ventricular cells were investigated with the action potential-clamp technique. Under current clamp, both agonists resulted in action potential shortening and a decrease in contraction. Under action potential clamp, both agonists failed to decrease contraction substantially. In the absence of agonist, application of the short action potential waveform (recorded previously in the presence of agonist) also resulted in a decrease in contraction. Under action pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…Several reports demonstrated that muscarinic stimulation inhibits inward rectifier K + -channels, e.g., in rat locus coeruleus neurons (Shen et al, 1992), in cardiac muscle cells (Dobrzynski et al, 2002) and in rat prefrontal cortex pyramidal neurons (Carr et al, 2007). Shen & North (Shen et al, 1992) presented a mathematical model of the two conductance alterations, activation of a cation conductance and inactivation of an inward rectifier K + -conductance, for the muscarine-induced depolarization in the neurons.…”
Section: The Inactivation Of a Potassium Conductancementioning
confidence: 99%
“…Several reports demonstrated that muscarinic stimulation inhibits inward rectifier K + -channels, e.g., in rat locus coeruleus neurons (Shen et al, 1992), in cardiac muscle cells (Dobrzynski et al, 2002) and in rat prefrontal cortex pyramidal neurons (Carr et al, 2007). Shen & North (Shen et al, 1992) presented a mathematical model of the two conductance alterations, activation of a cation conductance and inactivation of an inward rectifier K + -conductance, for the muscarine-induced depolarization in the neurons.…”
Section: The Inactivation Of a Potassium Conductancementioning
confidence: 99%
“…Under physiological ionic conditions, the muscarinic receptor-mediated current is carried with a reversal potential between -10 and 0 mV, whereby depolarization is produced; thus, the discharge of action and slow-wave potentials initiates or accelerates unless the depolarization is extremely strong (31,32). Previous studies have shown that ACh activates and modulates the activity of GIRK channels in esophageal SMCs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Even in the case when agonist/antagonist affects only one population of receptors, signal transduction pathways often couple to more than one ionic current; AP-clamp is uniquely suited for studying the drug concentration-dependent effects on multiple currents. As example, the frequency-dependent effects of isoproterenol on I Ca,L , I Ks , and I Cl in guinea pig ventricular cells (Rocchetti et al, 2006) and the effects of acetylcholine and adenosine on I K1 in ferret cardiac myocytes (Dobrzynski et al, 2002) were clarified using the AP-clamp technique.…”
Section: Characterization Of Drug Effectsmentioning
confidence: 99%